2007
DOI: 10.1002/humu.9485
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of NPHP6/CEP290 mutations in Leber congenital amaurosis and delineation of the associated phenotype

Abstract: Leber congenital amaurosis (LCA) is the earliest and most severe retinal degeneration responsible for congenital blindness. Hitherto, 13 LCA genes have been mapped, nine of which have been identified. Recently, mutations in the NPHP6/CEP290 gene were shown to account for Joubert and Senior-Loken syndromes and to represent a frequent cause of isolated LCA. All LCA patients shared an intronic mutation resulting in an aberrantly spliced transcript and low levels of wild-type transcript that was believed to explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
201
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(219 citation statements)
references
References 17 publications
12
201
0
6
Order By: Relevance
“…Despite these differences, it is apparent that sensory cells are much more susceptible to mutations in CEP290 than other ciliary systems. Nonsense mutations of CEP290 result in Joubert syndrome, characterized by retinal degeneration, cerebellar vermis aplasia, and nephronophthisis, and Meckel syndrome, an autosomal recessive lethal condition characterized by CNS, kidney, and liver malformations (15,21,22,25). Missense mutations (such as those detected in LCA and the rd16 mice), however, appear to only affect sensory systems, resulting in retinal degeneration and olfactory dysfunction in both humans and mice, with no overt kidney or cerebellar defects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences, it is apparent that sensory cells are much more susceptible to mutations in CEP290 than other ciliary systems. Nonsense mutations of CEP290 result in Joubert syndrome, characterized by retinal degeneration, cerebellar vermis aplasia, and nephronophthisis, and Meckel syndrome, an autosomal recessive lethal condition characterized by CNS, kidney, and liver malformations (15,21,22,25). Missense mutations (such as those detected in LCA and the rd16 mice), however, appear to only affect sensory systems, resulting in retinal degeneration and olfactory dysfunction in both humans and mice, with no overt kidney or cerebellar defects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in LCA revealed the intronic CEP290 variant c.2991+1655A4G as the most frequent in the Caucasian population, explaining~12% of cases in Caucasian populations originating from North-West Europe. [13][14][15] In addition, the AIPL1 variant p.(W278*) in exon 6, a conspicuous cluster of CRB1 variants in exons 7 and 9, and the GUCY2D exon 12 variant p.(R768W) together may explain~14% of the cases. 16,17 Therefore, prescreening of these 5 exons potentially identifies 26% of the mutations, serving as a cost-and time-effective genotyping procedure for LCA.…”
Section: Introductionmentioning
confidence: 99%
“…CEP290 mutations have been described in up to 20% of cases of the devastating inherited blinding disease Leber congenital amaurosis (7,8) and in numerous cases of other more debilitating ciliopathies, such as Joubert syndrome (9-11), Senior-Løken syndrome (12), and Meckel-Gruber syndrome (13). How the many identified mutations in CEP290 contribute to these diverse pathologies remains unknown, and the protein's normal biological role has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%